Rights of women in the establishment and dissolution of marriage in Oman: between CEDAW and sharia perspective - Aghbari, Fahad Al; Hassan, Muhamad Sayuti; Mamari, Saleh Al; Musa, Nurhafilah (Faculty of Law, University of Muhammadiyah Malang, 2024)
The Sultanate of Oman has acceded to CEDAW in 2005. However, Oman has reservations about a few articles of the said Convention because some of its provisions conflict with Islamic Sharia or Oman's national laws, including Article 16 of CEDAW. Therefore, the objective of this article is to critically analyse Article 16 of CEDAW and the extent to which Oman Personal Status Law addresses marriage and divorce-related issues is compatible or in conflict with the Convention. To accomplish this objective, the research employs doctrinal legal research and an analytical approach to examine the texts of the Convention and their Omani equivalents. The analysis revealed that the courts could enforce the articles of CEDAW to assert rights, except for the provisions that Oman expressed reservations about. Oman has reservations regarding several features outlined in Article 16 of the aforementioned Convention, as they conflict with Islamic Law. The study highlights that the Convention effectively governs certain areas that promote gender equality in family matters, including stipulating that a woman's permission is necessary for marriage and her entitlement to dissolve the marital union by divorce or khulu' under appropriate circumstances. In addition, Oman effectively implements certain provisions of the Convention to strengthen women's rights by modifying domestic legislation. In conclusion, the Oman National Law is consistent with the CEDAW, except for the State's reservations concerning the implementation of Article 16 of the aforementioned Convention.